Amorphous silicon active pixel sensor readout circuit for digital imaging. - Karim, K.S (IEEE Transactions on electron devices)
The most widely used architecture in large-area amorphous silicon (a-Si) flat panel imagers is a passive pixel sensor (PPS), which consists of a detector and a readout switch. While the PPS has the advantage of being compact and amenable toward high-resolution imaging, reading small PPS output signals requires external column charge amplifiers that produce additional noise and reduce the minimum readable sensor input signal. This work presents a current-mediated amorphous silicon active pixel readout circuit that performs on-pixel amplification of noise-vulnerable sensor input signals to minimize the effect of external readout noise sources associated with "off-chip" charge amplifiers. Results indicate excellent small-signal linearity along with a high, and programmable, charge gain. In addition, the active pixel circuit shows immunity to shift in threshold voltage that is characteristic of a-Si devices. Preliminary circuit noise results and analysis appear promising for its use in noise-sensitive, large-area, medical diagnostic imaging applications such as digital fluoroscopy.